A Review of Pathfinding in Game Development - Pardede, Sara Lutami; Athallah, Fadel Ramli; Huda, Yahya Nur; Zain, Fikri Dzulfiqar (Universitas Telkom, 2022)
Pathfinding is one important method in many studies or works that consists of autonomous movement, such as robot, game, transportation, and so on. Pathfinding aims to find the most efficient route for the related autonomous entity. To date, there are many algorithms regarding to the pathfinding. Especially, there are four well-known pathfinding algorithms: A*, Theta*, Dijkstra, and Breadth First Search (BFS). Due to this circumstance, this work aims to observe and review these four well-known algorithms deeper. The discussion consists of the conceptual model or framework, the formalization, and the implementation. The result shows that these algorithms have been implemented in many game so that they are promising to be used in the future game development.